Low Molecular Weight Heparin-Induced Skin Necrosis: A Case Report. (30th May 2011) - Katsourakis, Anastasios; Noussios, George; Kapoutsis, George; Chatzitheoklitos, Efthimios
Abstract : Low molecular weight heparins (LMWHs) are the standard agents used for antithrombotic therapy and prophylaxis. Despite their widespread use, reports about adverse effects from LMWHs are very scarce. Heparin-induced skin necrosis at the injection site is a rare adverse effect, more commonly associated with unfractionated heparin (UFH) rather than with LMWH, while its mechanism remains unclear. This paper deals with the enoxaparin induced skin necrosis.